2016
DOI: 10.1111/mcn.12408
|View full text |Cite
|
Sign up to set email alerts
|

Iodine status and associations with feeding practices and psychomotor milestone development in six‐month‐old South African infants

Abstract: Iodine is important for normal growth and psychomotor development. While infants below 6 months of age receive iodine from breast milk or fortified infant formula, the introduction of complementary foods poses a serious risk for deteriorating iodine status. This cross-sectional analysis assessed the iodine status of six-month-old South African infants and explored its associations with feeding practices and psychomotor milestone development. Iodine concentrations were measured in infant (n = 386) and maternal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 43 publications
0
13
0
2
Order By: Relevance
“…There were three qualitative studies. [10][11][12] In the articles included in the review, breastfeeding estimates were made by asking about the current situation and by recall of past behaviour, and complementary feeding practices were obtained by the food frequency, [13][14][15][16][17] 24-hour 14,16-23 and 7-day recall of foods. Four studies 1,13,24,25 used the WHO IYCF indicators.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There were three qualitative studies. [10][11][12] In the articles included in the review, breastfeeding estimates were made by asking about the current situation and by recall of past behaviour, and complementary feeding practices were obtained by the food frequency, [13][14][15][16][17] 24-hour 14,16-23 and 7-day recall of foods. Four studies 1,13,24,25 used the WHO IYCF indicators.…”
Section: Resultsmentioning
confidence: 99%
“…• < 1% were exclusively breastfed up to 6 months 17 • < 1% were exclusively breastfed at 24 weeks 22 • 6% of < 1-month-5-month-olds were exclusively breastfed 36 • 7.6% of < 12-month-olds were exclusively breastfed 37 • 12% were exclusively breastfed for 6 months 21 • 13% were exclusively breastfed for 6 months 13 • 18% were exclusively breastfed at 14 weeks 32 • 27% of 0-10-month-olds were exclusively breastfed 33 • 29.5% were exclusively breastfed at 30 days 19 • 35.6% of 3-6-month-olds were exclusively breastfed 31 • 36.5% were exclusively breastfed > 3 months 38 • 38.5% of < 6-month-olds were exclusively breastfed 24 • 40% of HIV positive and 45% of HIV negative mothers exclusively breastfed for 6 months 34 • 52% were not exclusively breastfed beyond 2 months 15 • 61.8% were exclusively breastfed in HIV infected mothers and 72.6% were exclusively breastfed in HIV uninfected mothers at 3-4 months 29 Three studies reported that there was no exclusive breastfeeding in the surveyed community 12,16,30 The duration of exclusive breastfeeding reported in studies was not standardised and this makes it difficult to draw any conclusions about this aspect of IYCF…”
Section: Criteria Findingmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychomotor and socio-emotional development of the offspring is being assessed using the Protocol for Child Monitoring –Infant version (PCM-I), which combines both parental report and direct observation by trained assessors to provide a comprehensive evaluation of a child’s motor skills, cognition, language, personal and socio-emotional development [ 62 ]. The PCM-I consists of items derived from: 1) the Kilifi Developmental Inventory (KDI) [ 63 ], previously used by the investigators to determine psychomotor development in an infant population in South Africa [ 64 ], 2) the Developmental Milestone Checklist (DMC-II) [ 65 , 66 ], and 3) the Profile of Social-Emotional Development (PSED), which is based in part on the Brief Infant/Toddler Social Emotional Assessment [ 67 ].…”
Section: Methodsmentioning
confidence: 99%
“…Iodine deficiency is associated with several abnormalities which are named as IDD (8) . Some complications of iodine deficiency include goitre, lack of physical and mental development, and poor learning ability in children (9)(10)(11) . Iodine deficiency also leads to abortion, stillbirth and congenital anomalies, and increases prenatal death and infant mortality (1,(12)(13)(14) .…”
mentioning
confidence: 99%